Serum levels of reduced glutathione, oxidized glutathione, and glutathione reductase activity in minor recurrent aphthous stomatitis patients - Zichuan Zhang; Qian Zhang; Yi Xue; Huiqing Fang; Zhongyin Wu (Elsevier, 2023)
Background/purpose: Recurrent aphthous stomatitis (RAS) is one of the most prevalent oral mucosa diseases with unknown etiology. Reduced glutathione (GSH) is a major intracellular non-protein physiological antioxidant, and it has been demonstrated that GSH deficiency may be related to cardiovascular, immune, and diabetes. The purpose of this investigation was to evaluate the potential roles of GSH, oxidized glutathione (GSSG), and glutathione reductase (GR) in the etiopathogenesis of minor recurrent aphthous stomatitis (MiRAS). Materials and methods: The study comprised 87 patients with idiopathic MiRAS and 90 race-, age-, and gender-matched healthy individuals. The spectrophotometric method was used to determine serum GSH and GSSG concentrations as well as GR activity. The GSSG/GSH ratios were subsequently computed. For statistical evaluation, the independent sample t test, Pearson's chi-square test, Mann-Whitney U test, Kruskal-Wallis H test, and Binary logistic regression analysis were used. Results: The serum GSSG level, GR activity and GSSG/GSH ratio were statistically higher in MiRAS patients, whereas the concentration of serum GSH was significantly decreased. With the exception of GR, serum GSSG, GSH, and GSSG/GSH were all significantly associated with MiRAS. Serum GSSG can be regarded as a risk factor, whereas serum GSH and GSSG/GSH maybe considered as protective factors against the occurrence of MiRAS. Conclusion: GSSG may be a potential danger factor to MiRAS and GSH may be a protective factor, while GR may not play an important role in the aetiopathogenesis of MiRAS.